Problematic Kurdish Negotiating with Iraqi Successive Governments From 1921-1992 From the Standopint of Elite Intellectuals Consider Kurds a Field Study in Kurdistan Region - Salih, Meran M. (Humanities Journal of University of Zakho, 2017)
The research is conducted to understand how the process of negotiation amongst the Kurdish leaders and Iraqi subsequent governments has been implemented from 1921until 1992; that is, it is a social and political process according to what the Kurdish intellectuals in Iraqi Kurdistan region believe. Besides, the research makes attempts to evaluate the foregoing process in terms of any changes and consequences that the Kurdish intellectuals identify for the improvement of Kurdish community in future. In fact, the significance of this research is to obtain a clear vision in indicating the reality of the Kurdish negotiators and representative as well as in identifying the weak points and obstacles facing the process of negotiation. Obviously, this is a field-conducted research associated with sociology and politics, and also it could be, to certain extend, useful for some other branches of sociology and politics. As far as the researcher is concerned, this is the first scientific research conducted in Kurdistan regional government. This study is to obtain several goals, they are: Displaying and categorizing the principles of negotiation. The significance of diplomatic relation and historical, political and economic condition of the Kurdish revolution during the negotiation. Making effort to scatter political awareness related to such an issue for those who are in politics and international relations; furthermore, it is an attempt for identifying the weak points of the former negotiation. In this study the historical method has been utilized for collecting data, and the researcher has used survey (questionnaire) and provided interview as the instrument of the research Additionally, the sample of the study (variables) is purposive; that is, 278 intellectuals from Hawler, Sulaimani, Duhok have participated in this study. We came to conclusion that: 39% of the participants emphasized on the reason of neglecting the freelance intellectuals and thinkers in participating in negotiation between Iraqi governments and the Kurdish revolution. 39% of the participants believed that the reason of failing in the negotiations is belongs to the dispute and quarrel among the Kurdish leaders themselves. 40% of the participants believed that the reason of failing on the negotiations is attributed to the lack of knowledge, carefulness, and erudition of the Kurdish leaders about the division power and authority in the territory among the powerful countries particularly in the Middle-East. 88.12% emphasized on the fact that there has not been any change among the Iraqi subsequent government in handling the Kurdish issue in Iraqi so far.